A polyunsaturated sulfobetaine containing glycidyl group and preparation method thereof
By grafting glycidyl-containing polyunsaturated sulfobetaine on the surface of the aromatic polyamide composite film with high density, the problems of biological pollution and chemical degradation of the composite film during seawater desalination are solved, significantly improving the film's pollution resistance and chlorine resistance, and extending its service life.
Patent Information
- Application Number
- CN202410946747.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-16
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-07-16
AI Technical Summary
The existing aromatic polyamide composite membranes are susceptible to marine biological pollution and chemical degradation of active chlorine during seawater desalination, resulting in a shortening of the membrane's service performance and life.
A polyunsaturated sulfobetaine containing glycidyl groups was developed, and the polyallyl ammonium type unsaturated sulfobetaine containing glycidyl groups was grafted on the membrane surface with high density to enhance the film's anti-fouling and chlorine resistance.
It effectively improves the anti-fouling, sterilization and chlorine resistance of the aromatic polyamide composite film, extends the service life of the film, and maintains the high mass transfer performance of the film.
Smart Images

Figure QLYQS_1 
Figure BDA0004945885430000021 
Figure BDA0004945885430000041
Abstract
Description
Technical Field
[0001] The invention relates to a zwitterionic crosslinking agent and a preparation method thereof, and particularly to a polyunsaturated sulfobetaine containing a glycidyl group in a chemical structure and a preparation method thereof. The polyunsaturated sulfobetaine containing a glycidyl group is used as a graft-modified crosslinking agent containing NH or OH in a polymer chain structure, and belongs to the field of functional polymer materials. Technical Background
[0002] At present, the reverse osmosis, nanofiltration and microfiltration membranes made of metaphenylenediamine and trimesoyl chloride as monomers deposited on the surface of the support membrane are the most commonly used commercial varieties of aromatic polyamide composite membranes. They have good separation performance, high mechanical strength and a wide temperature and pH tolerance range, and are widely used in seawater desalination, brackish water desalination, industrial sewage treatment, pure water production and other industries. However, the thorny problem in seawater desalination is the biological contamination of the membrane by marine organisms and the chemical degradation of the aromatic polyamide layer of the membrane by active chlorine. The marine biological contamination of the membrane refers to the adhesion, growth and reproduction of seawater microorganisms on the surface of the composite membrane to form an extremely stubborn biological layer, which is difficult to clean manually and seriously affects the working efficiency of the composite membrane; in order to solve the biological contamination of aromatic polyamide composite membranes by microorganisms during seawater desalination or sewage treatment, seawater must be pre-treated and inactivated by chlorine. However, due to the chemical destruction of the aromatic polyamide active layer by trace amounts of chlorine and chlorine oxides remaining in seawater, the performance and life of the aromatic polyamide composite membrane are greatly shortened. Therefore, how to effectively control and reduce the pollution of aromatic polyamide composite membranes while ensuring the chemical stability of aromatic polyamide composite membranes has always been an important research topic in the field of aromatic polyamide composite membrane technology.
[0003] Over the years, researchers have developed a variety of membrane-making strategies and modification methods. Among them, it was found that grafting sulfonate betaine on the aromatic polyamide layer is effective in improving the marine antifouling ability of the membrane. On the one hand, sulfonate betaine has excellent hydrophilicity, improves the permeability of the membrane, and promotes the transmission of water molecules through the membrane; at the same time, a thick layer of sulfonate betaine with appropriate thickness combines a large number of water molecules on the membrane surface to form an elastic hydration layer, preventing the adhesion or deposition of microorganisms or inorganic salts on the membrane surface, ensuring the antifouling ability of the membrane; some other structures of quaternary ammonium salts and sulfonate betaine also have high biocidal activity and can resist the adhesion and growth of marine organisms. There are also many ways to improve the chlorine resistance of aromatic polyamide composite membranes. Among them, the more convenient and effective method is to graft chlorine-blocking structures or chlorine-consuming units on the surface of the composite membrane.
[0004] Although the surface modification of aromatic polyamide composite membranes requires additional membrane preparation steps and the operation process is prolonged, the grafting of the membrane surface will hardly have a significant impact on the structure of the original aromatic polyamide active separation layer, and the retention performance of the membrane remains basically unchanged. However, if the material for the membrane surface grafting is not properly selected, the membrane mesh will be clogged, the mass transfer resistance of the membrane will often increase, and the membrane water flux will decrease. Over the past decade, our research group has changed the modifiers such as polyethylene glycol quaternary ammonium salt, multifunctional polyurethane prepolymer, 2-hydroxy-3-(chlorinated N-glycidyl-N-alkyl-N-allyl ammonium) propyl phosphonate, 3-(N-glycidyl-N-alkyl-N-allyl ammonium) propyl-1-sulfonate, etc., and grafted polyethylene glycol chains, quaternary ammonium cations, salicylaldehyde, etc. on the surface of aromatic polyamide composite membranes, achieving a significant improvement in the hydrophilicity of the aromatic polyamide composite membrane surface, a significant improvement in the anti-marine biofouling function, and a significant improvement in the chlorine consumption effect and membrane water flux. Recently, we have found that grafting allyl ammonium type unsaturated phosphonates or unsaturated sulfonated betaines on the surface of aromatic polyamide composite membranes can not only improve various properties of the membrane surface, but also significantly improve the chlorine resistance. The main principle is that after grafting allyl ammonium type unsaturated phosphonates or unsaturated sulfonated betaines on the surface of aromatic polyamide composite membranes, the allyl ammonium type ions can consume Cl2 or chlorine oxides in water under normal conditions, preventing Cl2 or chlorine oxides from chemically degrading the active layer of the aromatic polyamide composite membrane, which has a positive effect on ensuring the membrane desalination capacity and water permeability. Based on this, the inventors have combined the purpose and requirements of surface modification of aromatic polyamide composite membranes and created a polyunsaturated sulfobetaine containing a glycidyl group. Also under mild conditions, the polyunsaturated sulfobetaine can undergo a ring-opening reaction with an aromatic polyamide composite membrane containing an amino group on its surface, and graft polyallyl ammonium-type unsaturated sulfobetaine on the surface of the aromatic polyamide composite membrane in a single-layer manner and with a high-density effect in one step. The purpose is to graft more allyl ammonium ions on the surface of the aromatic polyamide composite membrane, thereby achieving higher chlorine consumption capacity and more durable protective film, thereby laying a material foundation for simultaneously improving the hydrophilicity, bactericidal and antifouling properties and chlorine resistance of the surface of the aromatic polyamide composite membrane. Summary of the invention
[0005] The present invention provides a polyunsaturated sulfobetaine containing a glycidyl group, which has a chemical structure shown in the general formula (I):
[0006]
[0007] Wherein R in the general formula (Ⅰ) is selected from C1 to C 18 Hydrocarbon group, n is a natural number between 0 and 200.
[0008] The specific preparation method of the polyunsaturated sulfonate containing glycidyl groups of the present invention is as follows: respectively weigh a solvent, double-terminated (N-alkyl-N-allylamino) polyethylene glycol, 1,3-propane sultone and a polymerization inhibitor into a reactor, and under N2 protection, adjust the temperature of the materials in the reactor to 30-90°C, stir and react for 6-20 hours, then reduce the temperature of the materials in the reactor to room temperature, separate the solvent layer in the reactor, and then add an organic solvent, epichlorohydrin and a polymerization inhibitor into the reactor, and under N2 protection, increase the temperature of the materials in the reactor to 60-90°C, stir and react for 6-20 hours, then reduce the temperature of the reaction product system to room temperature, filter, wash and dry to obtain the polyunsaturated sulfonate containing glycidyl groups of the general formula (I).
[0009] The amount of 1,3-propane sultone is 0.8 to 1.5 times the molar amount of double-terminal (N-alkyl-N-allylamino) polyethylene glycol, the amount of epichlorohydrin is 1.2 to 2.2 times the molar amount of double-terminal (N-alkyl-N-allylamino) polyethylene glycol, the amount of the polymerization inhibitor is 0.3 to 3% of the mass of double-terminal (N-alkyl-N-allylamino) polyethylene glycol, the amount of the solvent is 0.5 to 1.0 times the sum of the masses of double-terminal (N-alkyl-N-allylamino) polyethylene glycol and epichlorohydrin, and the amount of the organic solvent is 0.5 to 5.0 times the sum of the masses of double-terminal (N-alkyl-N-allylamino) polyethylene glycol, epichlorohydrin and 1,3-propane sultone.
[0010] The alkyl group in the double-terminal (N-alkyl-N-allylamino) polyethylene glycol refers to C1~C 18 Hydrocarbon.
[0011] The solvent refers to one or more of diethyl ether, tetrahydrofuran, 1,4-dioxane, ethyl acetate, acetone, butanone, chloroform, 1,2-dichloroethane, carbon tetrachloride, toluene or chlorobenzene.
[0012] The organic solvent refers to one or more of methanol, ethanol, propanol, acetonitrile, dimethyl sulfoxide, N-methylpyrrolidone, N,N-dimethylformamide or N,N-dimethylacetamide.
[0013] The polymerization inhibitor refers to one or more of hydroquinone, p-methoxyphenol, tert-butylhydroquinone, 2,6-dibutylhydroquinone, 2,6-di-tert-butyl-p-cresol or 2,4,6-tri-tert-butylphenol.
[0014] The beneficial effects of the polyunsaturated sulfobetaine containing glycidyl provided by the present invention are:
[0015] (1) The present invention provides the polyunsaturated sulfobetaine containing glycidyl groups, which is mainly used for the cross-linking modification of the ring-opening grafting and polymerization grafting of starch, cellulose, polyurethane, polyamide, polyester, etc. containing amino groups or hydroxyl groups in the polymer chain structure. The new functional polymer material prepared thereby has high chemical stability in acidic and alkaline environments, and is multifunctional and efficient.
[0016] (2) The polyunsaturated sulfobetaine containing glycidyl groups described in the present invention is used as a zwitterionic functional monomer, which has a scientific structure, comprehensive functions, optimized technology and superior performance.
[0017] ⑶ The raw materials required for preparing the polyunsaturated sulfobetaine containing glycidyl groups of the present invention are all industrial products, the raw materials are easily available, the preparation method is simple, the product purification is simple, and the process is safe and efficient. DETAILED DESCRIPTION
[0018] The following examples further illustrate the polyunsaturated sulfobetaine containing glycidyl groups and the preparation method thereof provided by the present invention, the purpose of which is to provide a better understanding of the present invention.
[0019] Example 1 Preparation of polyunsaturated sulfobetaine (1) containing glycidyl groups
[0020] Weigh 80 g of tetrahydrofuran, 50 g of β,β'-di(N,N-diallylamino)diethyl ether, 25 g of 1,3-propanesultone, and 1.03 g of 2,6-di-tert-butyl-p-cresol into a reactor. Under N2 protection, control the temperature of the materials in the reactor to 60-65°C, stir and react for 16 hours, terminate the reaction, lower the temperature of the reaction product system to room temperature, separate the upper tetrahydrofuran, and then add 110 g of methanol and 30 g of epichlorohydrin. and 1.05 g of 2,6-di-tert-butyl-p-cresol were put into the reactor. Under N2 protection, the temperature of the materials in the reactor was controlled to 70-75°C. After stirring for 20 hours, the temperature of the reaction product system was lowered to room temperature. After filtration, methanol washing, and vacuum drying to constant weight, 81.5 g of white crystalline product was obtained. The melting range was 115.0-118.5°C. The product yield was 90.1% based on β,β'-di(N,N-diallylamino)diethyl ether. The Cl in the product was measured by titration analysis. - The content is 7.44%, which is consistent with the set molecular formula C 22 H 39 ClN2O5S Calculation Theory Cl - The content is 7.40% basically consistent; the IR data of the product (KBr tablet): 3029cm -1 Characteristic absorption peaks of C=CH, 2937, 2858cm -1 The characteristic absorption peak of methylene and methine is 1637cm -1 It is the characteristic absorption peak of C=C, 1448cm-1 It is the characteristic absorption peak of CN, 1048cm -1 Characteristic absorption peaks of S=O, 1016, 975cm -1 The center is the characteristic absorption peak of COC ring; 1 H-NMR (δ, D2O): 2.27 (m, 2H), 2.72 (d, 2H), 3.10 (m, 1H), 3.22-3.24 (m, 4H), 3.41-3.43 (m, 6H), 3.81 (m, 4H), 3.93 (m, 8H), 5.41 (m, 8H), 5.72 (m, 4H). The above structural analysis and characterization showed that the white crystalline product should have the following structural characteristics:
[0021]
[0022] Example 2 Preparation of polyunsaturated sulfobetaine (2) containing glycidyl groups
[0023] Weigh 60 g of tetrahydrofuran, 33 g of double-terminated (N,N-diallylamino) triethylene glycol, 15 g of 1,3-propane sultone, and 0.83 g of 2,6-di-tert-butyl-p-cresol into a reactor. Under N2 protection, control the temperature of the materials in the reactor to 60-65°C, stir and react for 20 hours, terminate the reaction, lower the temperature of the reaction product system to room temperature, separate the upper tetrahydrofuran, and then add 80 g of ethanol and 18 g of epichlorohydrin. 0.83 g of 2,6-di-tert-butyl-p-cresol and 0.83 g of 2,6-di-tert-butyl-p-cresol were put into the reactor. Under N2 protection, the temperature of the materials in the reactor was controlled to 60-65°C. After stirring for 20 hours, the temperature of the reaction product system was lowered to room temperature. After filtration, ethanol washing, and vacuum drying to constant weight, 51.9 g of pure product was obtained, with a melting range of 98.5-102.5°C. The product yield was 92.8% based on double-terminated (N,N-diallylamino) triethylene glycol. The product was confirmed to have the following structural characteristics through structural analysis and characterization:
[0024]
[0025] Example 3 Preparation of polyunsaturated sulfobetaine (3) containing glycidyl groups
[0026] 80 g of tetrahydrofuran, 50 g of double-terminated (N, N-diallylamino) polyethylene glycol-200, 13 g of 1,3-propane sultone, and 0.85 g of 2,6-di-tert-butyl-p-cresol were weighed and put into a reactor. Under N2 protection, the temperature of the materials in the reactor was controlled to 60-65°C. The reaction was stirred for 20 hours. The reaction was terminated, the temperature of the reaction product system was lowered to room temperature, and the upper tetrahydrofuran was separated. Subsequently, 110 g of methanol, 15.3 g of epichlorohydrin and 0.85 g of 2,6-di-tert-butyl-p-cresol were added to the reactor. Under N2 protection, the temperature of the materials in the reactor was controlled to 70-75°C. After stirring for 20 hours, the temperature of the reaction product system was lowered to room temperature. After filtering, washing with methanol, and vacuum drying to constant weight, 62.2 g of a paste product was obtained. The product yield was 85.6% based on double-terminated (N, N-diallylamino) polyethylene glycol-200. Through structural analysis and characterization, it is confirmed that this paste product has the following structural characteristics:
[0027]
[0028] Example 4 Preparation of polyunsaturated sulfobetaine (4) containing glycidyl groups
[0029] Weigh 80 g of tetrahydrofuran, 50 g of β,β'-di(N-benzyl-N-diallylamino)diethyl ether, 18 g of 1,3-propanesultone, and 1.03 g of 2,6-di-tert-butyl-p-cresol into a reactor. Under N2 protection, control the temperature of the materials in the reactor to 60-65°C, stir and react for 16 hours, terminate the reaction, lower the temperature of the reaction product system to room temperature, separate the upper tetrahydrofuran, and then add 110 g of isopropanol and 17.3 g of epichlorohydrin. 1.05 g of 2,6-di-tert-butyl-p-cresol and 1.05 g of 2,6-di-tert-butyl-p-cresol were put into the reactor. Under N2 protection, the temperature of the materials in the reactor was controlled to 70-75°C. After stirring for 20 hours, the temperature of the reaction product system was lowered to room temperature. After filtration, washing with isopropanol, and vacuum drying to constant weight, 71.5 g of white crystalline product was obtained, with a melting point of 136.0-138.5°C. The product yield was 91.5% based on β,β'-di(N-benzyl-N-diallylamino)diethyl ether. The structural analysis and characterization confirmed that the white crystalline product had the following structural characteristics:
[0030]
[0031] Example 5 Preparation of polyunsaturated sulfobetaine (5) containing glycidyl groups
[0032] Weigh 80 g of tetrahydrofuran, 50 g of β,β'-di(N-dodecyl-N-diallylamino)diethyl ether, 13 g of 1,3-propanesultone, and 1.3 g of 2,6-di-tert-butyl-p-cresol into a reactor. Under N2 protection, control the temperature of the materials in the reactor to 60-65°C, stir and react for 20 hours, terminate the reaction, lower the temperature of the reaction product system to room temperature, separate the upper tetrahydrofuran, then add 70 g of isopropanol, epoxy 10.3 g of chloropropane and 1.05 g of 2,6-di-tert-butyl-p-cresol were put into the reactor. Under N2 protection, the temperature of the materials in the reactor was controlled to 70-75°C. After stirring for 20 hours, the temperature of the reaction product system was lowered to room temperature. After filtration, washing with isopropanol, and vacuum drying to constant weight, 61.7 g of white crystalline product was obtained, as β,β'-di(N-dodecyl-N-diallylamino)diethyl ether, with a product yield of 78.7%. After structural analysis and characterization, it was confirmed that this white crystalline product has the following structural characteristics:
[0033]
[0034] Example 6 Characteristics of polyunsaturated sulfobetaines containing glycidyl groups in Examples 1 to 5
[0035] Prepare a 20% mass percentage concentration of the polyunsaturated sulfobetaine aqueous solution containing glycidyl groups in Examples 1 to 5, and mix 2 mL of the polyunsaturated sulfobetaine aqueous solution containing glycidyl groups in Examples 1 to 5 with different concentrations with 10 mL of culture medium according to dilution ratios of 1:2, 1:10, 1:50, 1:100, 1:1000, and 1:10000, add 2 drops of pathogenic bacteria suspension, mix well, and culture in a 37° C. incubator for 24 hours; observe the growth of pathogenic bacteria, calculate the minimum inhibitory concentration (MIC), and the test results are shown in Table 1.
[0036] Table 1 Antibacterial test results
[0037]
[0038] It can be seen from the antibacterial experiment in Table 1 that the polyunsaturated sulfobetaine containing a glycidyl group of the present invention has a high antibacterial activity, and the antibacterial activity is significantly improved by introducing a benzyl group or a dodecyl group on the N atom of the quaternary ammonium.
Claims
1. A polyunsaturated sulfobetaine containing a glycidyl group, which has a chemical structure shown in the general formula (I): ; Wherein R in the general formula (Ⅰ) is selected from C1~C 18 Hydrocarbon group, n is a natural number between 0 and 5.
2. A method for preparing the glycidyl-containing polyunsaturated sulfobetaine according to claim 1, characterized in that The preparation method of the polyunsaturated sulfonate containing glycidyl groups is achieved by the following method: respectively weighing a solvent, double-terminated (N-alkyl-N-allylamino) polyethylene glycol, 1,3-propane sultone and a polymerization inhibitor into a reactor, and regulating the temperature of the materials in the reactor to 30-90° C. under N2 protection, stirring and reacting for 6-20 hours, lowering the temperature of the materials in the reactor to room temperature, separating the solvent layer in the reactor, and then adding an organic solvent, epichlorohydrin and a polymerization inhibitor into the reactor, and raising the temperature of the materials in the reactor to 60-90° C. under N2 protection, stirring and reacting for 6-20 hours, and then lowering the temperature of the reaction product system to room temperature, filtering, washing and drying to obtain the polyunsaturated sulfonate containing glycidyl groups of the general formula (I); The alkyl group in the double-terminated (N-alkyl-N-allylamino) polyethylene glycol refers to C1~C 18 Hydrocarbon; The amount of the 1,3-propane sultone is 0.8 to 1.5 times the molar amount of the double-terminal (N-alkyl-N-allylamino) polyethylene glycol, the amount of epichlorohydrin is 1.2 to 2.2 times the molar amount of the double-terminal (N-alkyl-N-allylamino) polyethylene glycol, the amount of the polymerization inhibitor is 0.3 to 3% of the mass of the double-terminal (N-alkyl-N-allylamino) polyethylene glycol, the amount of the solvent is 0.5 to 1.0 times the sum of the masses of the double-terminal (N-alkyl-N-allylamino) polyethylene glycol and epichlorohydrin, and the amount of the organic solvent is 0.5 to 5.0 times the sum of the masses of the double-terminal (N-alkyl-N-allylamino) polyethylene glycol, epichlorohydrin, and 1,3-propane sultone.
3. The method for preparing the glycidyl-containing polyunsaturated sulfobetaine according to claim 2, characterized in that The solvent refers to one or more of diethyl ether, tetrahydrofuran, 1,4-dioxane, ethyl acetate, acetone, butanone, chloroform, 1,2-dichloroethane, carbon tetrachloride, toluene or chlorobenzene.
4. The method for preparing the glycidyl-containing polyunsaturated sulfobetaine according to claim 2, characterized in that The organic solvent refers to one or more of methanol, ethanol, propanol, acetonitrile, dimethyl sulfoxide, N-methylpyrrolidone, N,N-dimethylformamide or N,N-dimethylacetamide.
5. The method for preparing the glycidyl-containing polyunsaturated sulfobetaine according to claim 2, characterized in that The polymerization inhibitor refers to one or more of hydroquinone, p-methoxyphenol, tert-butylhydroquinone, 2,6-dibutylhydroquinone, 2,6-di-tert-butyl-p-cresol or 2,4,6-tri-tert-butylphenol.
Citation Information
Patent Citations
Multifunctional diallylammonium monomer and preparation method thereof
CN116987260A
Hydroxysultaine- and sulfobetaine-based geminal zwitterionic liquids, method for obtaining same, and use thereof as wettability modifiers having corrosion inhibiting properties
US20170320817A1